EFFECT OF DIFFERENT HERBAL-BASED INTRACANAL IRRIGATION SOLUTIONS ON BACTERIAL INHIBITION AND DENTIN ROUGHNESS OF ROOT CANAL IN PRIMARY TEETH (Journal of Pharmaceutical Negative Results, 2022)
Background: Intracanal irrigants are considered one of the most important factors for the success of root canal therapy, especially in primary teeth. Recently, many researchers directed their research toward the use of biological medicines of herbal origin due to their multiple benefits. Accordingly, the current study aimed to evaluate the antimicrobial effect of Moringa, costus, and Star anise herbal intracanal irrigants, and their effect on dentin roughness.Methodology: Herbal extract of Moringa (Group 1), Costus (Group 2), and Star anise (Group 3) were specially prepared as experimental intracanal irrigants and were compared to two widely used irrigants; 0.5% NaOCl as positive control (Group 4) and 0.9% normal saline as a negative control (Group 5). These five groups were investigated for their antibacterial efficacy against Enterococcus faecalis (Subgroup A) and Candida Albicans (Subgroup B), in addition, to the effect of these irrigants on the surface roughness of human root canal dentin, after placing them in 200 distal roots of extracted primary molars for 15 minutes was studied.Results: Regarding the antibacterial effect, NaOCL shows the highest percent of reduction of both E. Faecalis and C. Albicans followed by Costus with no significant difference between the two groups. The highest mean decrease in surface roughness in both Sa and Sz parameters was in group 4 (NaOCL).Conclusion: Indian Costus shows a high antibacterial effect which is comparable to NaOCL with lower surface roughness that can decrease the adhesion of bacteria to the dentinal surface. On the other hand, the Sz parameter is considered a reliable method for measuring bacterial adhesion.